Effect of different cooking methods on formation of cholesterol oxidation products in pork and beef - Alina A.R.; Ummi Syuhada H.S.; Syazamawati Z.H.; Thema Juhana M.J.; Siti Mashitoh A.; Nurul Farah Sakinah A.; Nurul Mawaddah A.H.; Nurulhuda M.S. (2024)
Indexed by Scopus